A Study of Relationship Quality of Working Life and its Relation with the Productivity of Nurses in Hospitals in Qom: 2016 - Amirjafar Nazari; Khalil Alimohammadzadeh; Seyed Mojtaba Hosseini (Golestan University of Medical Sciences, 2019)
Background and objectives: Nurses' productivity is a worthy goal of organizations tending to grow. Improving nurse' QWL is a prerequisite to increase their productivity. The purpose of this study was to explore the relationship between quality of work-life (QWL) and productivity among nursing staff of hospitals of Qom, Iran. Methods: This descriptive-analytical study was performed on 250 individuals among nursing staff of private, public and social security hospitals of Qom, during 2016. The samples were selected by random sampling method. Data was collected using Mosadeghrad's survey of Quality of Work Life, Dehghan Nayeryand's productivity of questionnaire and demographic data questions. Using SPSS software (V22), data analysis was performed by Spearman  correlation. Results: Hospital nurses reported low QWL and moderate levels productivity. There were significant correlations between productivity and participation, job promotion, disturbance handling, communication, motivation for work, job security and job stress (P < 0.05). In addition, the result of spearman showed a significant relationship between productivity and one's QWL (p < 0.001, r=0.469). Conclusion: It is important to consider the QWL of the nurses to improve productivity and performance of the nurses. In addition, the managers should adopt appropriate policies to promote the QWL and productivity.